2019
DOI: 10.4049/jimmunol.1900285
|View full text |Cite
|
Sign up to set email alerts
|

IgM, IgG, and IgA Influenza-Specific Plasma Cells Express Divergent Transcriptomes

Abstract: Ab-secreting cells (ASC) or plasma cells are essential components of the humoral immune system. Although Abs of different isotypes have distinct functions, it is not known if the ASC that secrete each isotype are also distinct. ASC downregulate their surface BCR upon differentiation, hindering analyses that couple BCR information to other molecular characteristics. In this study, we developed a methodology using fixation, permeabilization, and intracellular staining coupled with cell sorting and reversal of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 58 publications
4
21
0
Order By: Relevance
“…Validating the observed differences, PB and GC transcriptional profiles appeared largely similar between organs (Figures S2D-S2K). The only detected difference was between IgA PB and others, as previously reported (Figure S2E) (Neu et al, 2019;Price et al, 2019). Thanks to our approach, we detected transcriptional differences in HA-Bmem between germline (likely GC-independent) and mutated (GC-dependent) cells, suggesting long term functional differences, depending on cell origin (Figures 3G and S2B).…”
Section: Resultssupporting
confidence: 81%
“…Validating the observed differences, PB and GC transcriptional profiles appeared largely similar between organs (Figures S2D-S2K). The only detected difference was between IgA PB and others, as previously reported (Figure S2E) (Neu et al, 2019;Price et al, 2019). Thanks to our approach, we detected transcriptional differences in HA-Bmem between germline (likely GC-independent) and mutated (GC-dependent) cells, suggesting long term functional differences, depending on cell origin (Figures 3G and S2B).…”
Section: Resultssupporting
confidence: 81%
“…Validating the observed differences, PB and GC transcriptional profiles appeared largely similar between organs ( Fig S2D-K). The only detected difference was between IgA PB and others, as previously reported ( Fig S2E) (Neu et al, 2019;Price et al, 2019). Thanks to the power of our approach, we detected transcriptional differences in Bmem and PB between germline (GCindependent) and mutated (GC-dependent) cells, suggesting long term functional differences, depending on cell origin (Fig 3G and Fig S2B and Fig S2L).…”
Section: Identification Of Bmem Precursors Using Scrna-seqsupporting
confidence: 84%
“…This analysis also revealed that despite differences in anatomical location, life span and proliferation status, plasma cells from the bone marrow and spleen, as well as splenic plasmablasts share a core transcriptional signature 11 . The expression of this gene signature is also largely independent of Ig isotype, with the exception of genes influencing homing and migration, which are differentially expressed between IgM + , IgG + and IgA + ASC populations 12 . In addition to the known regulators of ASC differentiation and function, most notably Irf4 , Prdm1 and Xbp1 (discussed below), genes within this signature encode proteins involved in a diverse range of cellular processes.…”
Section: Introductionmentioning
confidence: 88%